Islamic Justice Perspective On Notary The Perpetrators Criminal Action - Ira Alia Maerani (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
This study aims to find out to know the form of violations and witnesses to the notary position based on Law No. 2 of 2014 concerning the Position of Notary and the perspective of Islamic justice in viewing a notary who is indicated to have committed a crime in connection with an authentic deed he made. This research uses normative law research or dogmatic law research using the doctrinal method. Normative legal research includes research on legal principles, research on legal systematics, research on vertical and horizontal synchronization stages, comparison of law and legal history. This research concludes that the notary public is a public official who makes an authentic deed and has the authority as regulated in Article 15,16, 17 of Law No. 2 of 2014 concerning the Position of Notary Public. The notary is obliged to act on trust; honest; independent; objective and safeguard the interests of parties involved in legal actions. Notaries in carrying out their duties and positions if convicted of violations, may be subject to sanctions or sanctions in the form of civil, administrative, and notary code of ethics in accordance with Law of the Republic of Indonesia Number 2 of 2014 concerning Notary Positions. Even so, the Notary Position Law does not regulate criminal sanctions against Notaries. Whereas in practice there is an opportunity for a legal action or violation by a notary related to an authentic deed he made that can be qualified as a criminal offense. A notary who is indicated to have committed a crime in carrying out his authority as a Public Official, of course, must be a concern of the government and law enforcement because the law must be upheld against anyone who commits indiscriminate violations. This rule is a manifestation of the principle of